Atendimento psicanalítico on-line com crianças em tempo de pandemia. - Ferrari, Eduarda Vasconcelos (2023)
ICTs (Information and Communication Technologies) are a set of technologies that serve as mediators for communication processes and that have been enhanced thanks to the internet. These technologies have changed people's daily lives, influencing the way they work, relate, take care of their health and have fun, also generating new ways of learning. Psychology in the online modality is an increasingly present reality these days, mainly from online psychotherapy, which is a therapeutic process that takes place through digital platforms, such as video call, chat and e-mail applications. mail. This form of psychotherapy has gained prominence due to its practicality and accessibility. The COVID-19 pandemic, which occurred in early 2020, required social isolation as a measure to prevent the contamination and spread of the coronavirus, making online psychotherapy even more necessary. Therefore, also during this period, it was essential to welcome and continue the psychotherapeutic process with the children's audience online. This research had as its general objective to investigate the feasibility of psychotherapeutic services with children online, and as specific objectives to understand the motivations of the psychotherapist to continue the service with children, in the face of the pandemic, remotely, to list the existing techniques and mediations of the service online child psychotherapeutic; and to investigate the challenges encountered by professionals in this type of care for children, during the pandemic situation. For this, Laurence Bardin's content analysis was used, which consists of a methodology that aims to analyze data from a qualitative research based on the systematization of categories and themes present in the analyzed material. In this research, interviews were conducted with psychologists who assisted children online during the period of the COVID-19 pandemic through a psychoanalytical bias and it was observed that the pandemic was the main motivator for psychologists to start this work. Psychotherapy with children online is possible as long as there are necessary adaptations, such as changes in the therapeutic setting, including the service environment, mediators, therapeutic contract with children and their parents and the psychologist's knowledge of technologies and theory and technique of online psychotherapy.